Energy Harvesting System based on a Hydro Electric Generator for Smart Irrigation Systems - Oliveira, Luiz F. P.; Mello, Jessica M. [UNESP]; Duarte, Luis F. C.; Morais, Flavio J. O. [UNESP] (Institute of Electrical and Electronics Engineers (IEEE), 2024)
The world is advancing rapidly into the fourth industrial revolution, which focuses on developing cyber-physical systems. When aiming to achieve ultra-low power consumption requirements in applications involving self-powered Internet of Things (loT) devices in semi-structured scenarios, it is essential to specify not only energy harvesting techniques but also all other system components. This work presents the development of a simple timed irrigation system, without sensors, powered by a hydro generator. This system is designed to be energetically autonomous. The hydro generator was able to charge a supercapacitor in 2.09 % of the irrigation time for a once-A-day irrigation routine and 2.85 % of the irrigation time for a twice-daily irrigation routine, that is, it was capable of charging the system using very little irrigation time.
Keywords: Energy harvesting; hydro generators; Internet of Things; irrigation systems; ultra-low power systems